Can Health Insurance Protect Against Catastrophic Health Expenditures in Iran? A Systematic Review and Meta‐Analysis. Issue 4 (14th March 2021) - Soofi, Moslem; Arab‐Zozani, Morteza; Kazemi‐Karyani, Ali; Karamimatin, Behzad; Najafi, Farid; Ameri, Hosein
Abstract : The results of previous Iranian studies on the protective effect of health insurance on catastrophic health expenditures (CHE) are inconsistent. Therefore, the aim of this meta‐analysis was to summarize all existent evidence. We searched international and Iranian scientific databases for relevant literature. Using a Mantel–Haenszel random‐effects model, the pooled odds ratios (OR) were calculated. Subgroup meta‐analyses were performed considering the type of insurance and study population. The pooled OR for the protective effect of health insurance risk on facing CHE was 0.93 (95% confidence interval [CI], 0.68–1.28). The protective effect of the two types of insurance was statistically insignificant. Health insurance does not effectively provide financial protection against CHE in Iran. Expanding the prepayment mechanism and integrating health insurance funds can be good strategies in protecting people from CHE. More attention should be paid to the design of health insurance benefit package to cover chronic diseases.